Tomb of Sunan Gunung Jati and Pura Tanah Lot: Two Multi Religious Tourism Destination in Indonesia - MUNAWAR, Raniri; RAHMAT, Munawar; YAHYA, M. Wildan Bin H.M. (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).15, 2021)
Religious tourism destinations in Indonesia are an essential pillar in the development of a peaceful, pluralist society. Tourists of various ethnicities and religions mostly visit the spiritual tourism areas of SGJ (Tomb of SunanGunungJati, Cirebon West Java) and PTL (Pura Tanah Lot, Bali). Therefore, this research aims to discuss the impact of religious tourism on forming a pluralist and peaceful society. The method is qualitative research with data obtained through observation, short and in-depth interviews, and book surveys. The study subjects were three tour guides, 100 tourists at each location, with the field research carried out for 10 Friday nights each at SGJ (October 2019 to February 2020) and PTL (December 2018 to August 2019). The result showed that firstly tourists feel a spiritual aroma in religious tourism destinations. Secondly, SGJ tourists, in particular, feel confident that the prayers they say at SGJ's grave are answered. Thirdly, tourists visualize ethnicities and followers of other religions as brothers who share the same spiritual goals. The implication is that religious tourism destinations are an alternative to the formation of a peaceful pluralist society.